Rapid and Convenient Synthesis of Triarylpyridine Derivatives using Ammonium Carbamate as an Efficient Solid Ammonia Source Assisted by Microwave Irradiation - Mouradzadegun, Arash; Abadast, Fatemeh; Behzadi-Pasham, Fatemeh (Current Microwave Chemistry, 2015)
Ammonium carbamate can be used as a very effective reagent for preparation of 2,4,6- triarylpyridine derivatives from ring transformation of pyrylium salts under solvent-free conditions. The products are isolated without aqueous work-up in high purity and good yields. The microwave accelerated the reaction and renders the whole synthesis into a truly eco-friendly protocol.
Keywords: triarylpyridine